2015
DOI: 10.1111/arcm.12194
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Historical Cannonball from the Fortress of San Juan De Ulúa Exposed to a Marine Environment

Abstract: Metallurgical analyses and chemical characterizations were carried out on historical cannonballs from the Fortress of San Juan de Ulúa, Veracruz, México. Cannonballs dating from the 18th and 19th centuries share metallurgical characteristics similar to those of material coming from a shipment of ammunition found in the wreck of a sunken French ship from the battle of Trafalgar. The analyses show that the base material is grey cast iron with a carbon equivalent of 4.94 and a ferritic–perlitic matrix, in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
3
Order By: Relevance
“…The steadite is a ternary eutectic composed of austenite, cementite and iron phosphide (Fe 3 P) with at least 10 wt% of phosphorous. Eutectic grains surrounded by a cellular phosphide network have been observed in previous works [12,[20][21].of different phases in the sinters. That means that only the proportion of the phases in the samples changed.…”
Section: Microstructure Characterization By Sem-edx and Light Microscopymentioning
confidence: 64%
See 4 more Smart Citations
“…The steadite is a ternary eutectic composed of austenite, cementite and iron phosphide (Fe 3 P) with at least 10 wt% of phosphorous. Eutectic grains surrounded by a cellular phosphide network have been observed in previous works [12,[20][21].of different phases in the sinters. That means that only the proportion of the phases in the samples changed.…”
Section: Microstructure Characterization By Sem-edx and Light Microscopymentioning
confidence: 64%
“…The obtained values are in strong concordance with the resultant microstructure since the E1 bullet had a higher hardness value of around 500 HV. In the literature, it can be observed that the average hardness of this phosphide eutectic was around 482 HV and the pearlite 252 HV [12]. Therefore, the E1 bullet hardness values can be associated with a cast iron with high steadite content.…”
Section: Microhardness Measurementsmentioning
confidence: 85%
See 3 more Smart Citations